Comparative Evaluation of Enamel, Dentin, and Cementum Microstructure in Healthy and Periodontally Compromised Teeth: A Study of Oral Cavity Structures - Safdar, Shamayem; Khan, Azeem Gohar; Ali, Noman; Altaf, Junaid; Salahuddin, ,Muhammad Behzad; Rathore, Ehsan (Journal of Neonatal Surgery, 2025)
Background: Periodontal disease is a chronic inflammatory disease which mainly attacks the supporting parts of the teeth, but there is an increasing body of evidence suggesting that periodontal disease may also cause changes in the microstructure of dental hard tissues. Objective: To evaluate microstructure of enamel, dentin, and cementum of healthy and periodontally affected teeth. Methodology: This was a comparative cross-sectional study conducted in one of the tertiary care dental institutions, over a one-year time span. This was done on 100 permanent teeth extracted, both healthy and periodontologically compromised comprising 50 healthy teeth and 50 periodontally compromised teeth. The collection of samples was done using a non-probability purposive sampling. Descriptive statistics and inferential tests were utilized on the SPSS software to analyze and use descriptive statistics and appropriate tests. The p-value of less than 0.05 was observed to be significant. Findings: It was found that microstructural alterations of periodontally compromised teeth were significantly high compared to healthy teeth. The level of composite microstructural scoring was much higher in the periodontally compromised group indicating wide participation of hard tissues in periodontal disease. Conclusion: There are extreme enamel, dentin and cementum microstructural changes associated with periodontal disease. These findings do not just indicate that periodontal pathology does not just focus on the destruction of soft tissues, but it also shows that the integrity of the hard tissues needs to be considered when making a periodontal diagnosis and treatment planning.